Dynamics and diversity of innovation support services: especially networking service activities on selected agro-food innovation cases in Madagascar and Burkina Faso - Ndah, H.T.; Audouin, S.; Crestin-Billet, S.; Randrianarisona, N.; Andriamaniraka, H.; Toillier, A.; Traoré, O.; Fongang, G.; Mathé, S.; Knierim, A. (2021)
In this contribution, we have analysed the “dynamics and diversity of innovation support services, especially networking, facilitation and brokerage service situations as key for influencing successful outcome of innovation processes”?. Results indicate that service activities linked with “enhancing access to resources” and “offering capacity building, stand out as dominant across all three phases of innovation processes for the four innovation cases studied. This implies, support actors and beneficiaries of services seem to attach more importance to technical service activities (e.g. training) and access to resources (e.g. technical, financial resources) as well as facilitating market access over soft skills related service activities such as networking facilitation and brokerage, institutional support for niche innovations, advisory and consultancy and demand articulation. Nevertheless, a cross-cutting view of especially networking service activity reveals its presence in varied dynamics, diversity and forms. We, therefore, recommend that to enhance the key role of networking in any attempt at accompanying and supporting innovation processes, this service function: 1) should be considered as cross-cutting, embedded in every service function and service situation and 2) its specific activities should be sub-categorised under intended networking service activities and side-effect networking service activities all driven by both service providers and beneficiaries of these services for a better maximization of their expected impact on the success of targeted innovations under promotion.